The transformation of branding in logo designs (University of Basra as a model) - Al-Salman هاشم زكي محمد علي (Basrah Arts Journal, 2025)
Abstract: Study (The transformation of signs in slogans designs, Basra University as a model), deals with the first practice of humanity of symbols and signs within the caves that are considered simplified symbolic forms and significance for the old man, as the old man depends on simple vocabulary to facilitate their absorption and use, in addition to studying new stages in architecture of temples, buildings, groves and pyramids. Through this research, it can be said that the shift in the mark is one of the arts that accommodate events, intensify and reduce topics, and through the design we infer the signals and signs in the digital tool and technology this art can be developed in a way that keeps pace with the times, and the sign is the language of communication, in addition to the slogan is a visual indication of the characteristic of the scientific identity of a specific party and a specific product. Here the research problem was born in the following question: What are the signs of slogans designs and in particular Basra University? What are the changes that occurred on the slogan partial or radical, and what is the purpose of? Keywords: (Transformation – Brand – logo – Design)